Menelusuri Makna Primitif Dan Modern Dalam Cerpen "Matias Akankari" Karya Gerson POYK: Sebuah Analisis Struktural - Firsta Primordiyanti (LINGUISTIKA, 2011)
This article is a literary analysis on Gerson Poyk "Matias Akankari" by using structuralist approach. The focus of the analysis is on the theme of the story. It employs the theories of Todorov and Barthes that investigates the theme through syntactic, semantic, and pragmatic aspects. The meaning of primitive and modern is showed through the binary opposition in the analysis.